Archaeological theory in dialogue : situating relationality, ontology, posthumanism, and indigenous paradigms /: situating relationality, ontology, posthumanism, and indigenous paradigms. (2020) - Crellin, Rachel; Cipolla, Craig N, 1978-; Montgomery, Lindsay M (Lindsay Martel); Harris, Oliver J. T; Moore, Sophie V
No abstract available